2014
DOI: 10.1080/10508422.2014.934371
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV Status Among Female Youth With HIV

Abstract: Minority female youth are significantly affected by the HIV epidemic. The purpose of this pilot study was to explore sexual behavior practices, disclosure of HIV status, attitudes about disclosure, and knowledge of HIV disclosure laws among female youth with HIV (YWH). Findings suggest that the majority of YWH studied have been sexually active since their HIV diagnosis, although the nature and extent of sexual activity varied. Rates of nondisclosure to sexual partners varied based on the type of question asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In our study, low self-efficacy to disclose was significantly and negatively associated with the outcome variable. This can be explained by existing disclosure decision-making theories (Greene et al, 2012 ), and by studies highlighting the need for developing disclosure communication skills (Chenneville, Lynn, Peacock, Turner, & Marhefka, 2014 ). Recent studies showed that children considered accidental and deductive disclosure to be a substantial risk (Mupambireyi, Bernays, Bwakura-Dangarembizi, & Cowan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, low self-efficacy to disclose was significantly and negatively associated with the outcome variable. This can be explained by existing disclosure decision-making theories (Greene et al, 2012 ), and by studies highlighting the need for developing disclosure communication skills (Chenneville, Lynn, Peacock, Turner, & Marhefka, 2014 ). Recent studies showed that children considered accidental and deductive disclosure to be a substantial risk (Mupambireyi, Bernays, Bwakura-Dangarembizi, & Cowan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent qualitative study, trans and cis women detail why they stayed in abusive relationships under threat of prosecution were they to leave their partner or for fear of facing isolation (or worse) if needing to disclose their serostatus to another partner (Krüsi et al, 2018). Similar barriers to disclosure have been identified in youth living with HIV (Chenneville, Lynn, Peacock, Turner, & Marhefka, 2015;Gabbidon, Chenneville, Peless, & Sheared-Evans, 2020). In his address to the House of Commons, the director and lawyer of the HIV/AIDS Clinic in Ontario spoke about how his clients living with HIV often comment on the potential for a vindictive (ex-)partner approaching the police and pursuing legal recourse against them (e.g., Ryan Peck in House of Commons, 2019).…”
Section: Risk-benefit Analysismentioning
confidence: 83%
“…A recent systematic review concluded that fear surrounding disclosure was an important barrier to initiation of and adherence to ART, self-care, fulfilling a parental role, and a socially connected life (Evangeli & Wroe, 2017). This fear has led some PLWH to minimize or retire from romantic relationships entirely (Chenneville et al, 2015; Krüsi et al, 2018; Parsons, VanOra, Missildine, Purcell, & Gómez, 2004). One may want to consider what this means in terms of quality of life, mental health, and personal identity.…”
Section: Principle II Responsible Caringmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several country specific HIV laws [ 85 , 86 ], require people living with HIV to inform all their sex partners of their status. The utility of HIV criminalization laws as part of HIV prevention is still controversial [ 87 ].…”
Section: Discussionmentioning
confidence: 99%